Ambient Data Monitoring w/Generative Music Systems using EC & ML Techniques. - Roddy, Stephen (My University, 2018)
This is a position paper which describes work in progress to develop an AI/ML driven auditory ambient information system which incorporates generative music techniques and considers some of the factors involved the design and development of a system of this nature. The system is intended to represent and communicate information about cryptocurrency markets to a user. The generative music system uses evolutionary computing and machine learning techniques, which are driven by the original cryptocurrency data, to create musical information. This information is then mapped to synthesis parameters. The implementation described is web based running client-side in the browser. The paper describes the relevant background literature before presenting a generalised model for a system of this nature before discussing aspects of the implementation in its current state. The paper closes with a discussion of the system and future work.
Computer Simulation of Musical Creativity
PUBLISHED
Dublin
Keywords: Ambient Information System; Variational Autoencoder; Genetic Algorithm; Auditory Display; Sonic Information Design; Web Technologies; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Inclusive Society; Making Ireland; Smart & Sustainable Planet; Telecommunications; Auditory Display; HUMAN COMPUTER INTERACTION; Human-Computer Interaction; Internet of Things; MACHINE LEARNING; Music; Music Technology; ONLINE SYSTEMS; Smart Cities; Sonification; Communication; Culture; Home and community living; Policy